Natural Language Aided Visual Query Building for Complex Data Access - Pan, Shimei; Zhou, Michelle; Houck, Keith; Kissa, Peter (Proceedings of the AAAI Conference on Artificial Intelligence, 2010)
Over the past decades, there have been significant efforts on developing robust and easy-to-use query interfaces to databases. So far, the typical query interfaces are GUI-based visual query interfaces. Visual query interfaces however, have limitations especially when they are used for accessing large and complex datasets. Therefore, we are developing a novel query interface where users can use natural language expressions to help author visual queries. Our work enhances the usability of a visual query interface by directly addressing the "knowledge gap" issue in visual query interfaces. We have applied our work in several real-world applications. Our preliminary evaluation demonstrates the effectiveness of our approach